Characterization of Portland Cement Incorporated with FNS. (18th November 2020) - Cho, Won Jung; Kim, Min Jae; Lee, David Su Vin
Abstract : The potential use of ferronickel slag (FNS) as supplementary cementitious material has been widely researched in recent years. Although much research was carried out on utilizing FNS as a binder, its advantages and disadvantages are still not clear. To properly use FNS as a cement replacement, this paper summarizes the following. (1) Changes expected on the oxide composition of FNS powder are due to the forming ores, fluxing stone, and cooling method. (2) The decreasing of the hydration heat evolution rate was detected by hydration heat evolution test and this is due to the low content of CaO and Al2 O3 component in FNS. (3) It was found that the incorporation of FNS forms a dense pore structure more than cement mix and this is due to the secondary hydration reactions. (4) Hydration characteristics of FNS were assessed by pozzolanic reactions unexpectedly detected and incorporation of FNS creates C-S-H gel and hydrotalcite. (5) The development of strength was tested by compressive strength, splitting tensile strength, and flexural strength. From the results, the reduction of compressive strength was detected at an early age but substantially increasing at the long-term curing ages. However, splitting tensile strength and flexural strength of concrete have shown various trends. (6) There is an improvement in the resistance to chloride penetration and sulfate attack while susceptible to carbonation. This is induced by the lowered pH in pore solution due to the reduction of Ca(OH)2 by substituting FNS binder. Finally, (8) ternary blended mixtures with conventional cementitious materials are an option to properly use FNS as a binder.